O divórcio e a reconciliação da mesquita com estado: a constituição discursiva do sujeito mulher iraniana na escrita autobiográfica - Ferreira, Quézia Fideles (2016)
The constitution of the subject in all societies is closely linked to power relations established in a given historical moment. These relationships pervade the social practices and grounded in a set of knowledge, develop real desires that are incorporated by the subjects as "truths" absolute, unique and unquestionable. With regard specifically to the constitution of the subject Iranian woman, the development of their identity is tied to a particularized power system by a strong association between State and Religion, which has, over time, inferiorized the identity of the individual woman , seen as the other child before marriage to the father and then the celebration of the marriage agreement, the husband. Having as theoretical support the contributions from the Discourse Analysis, Foucault's research and cultural studies, this research we aim to analyze the constitution of the subject Iranian woman immersed in power relations in circulation in the course of the twentieth century, marked by profound changes political, social and historical. From this goal, we adopted as of this research investigation object the autobiographical novel What I did not tell, the Iranian author Azar Nafisi, whose first edition was translated into Portuguese in 2009, a year after its publication in the original Things I’ve been silent about. After our reflections, we found that the novel, narrated in first person, can be understood as an intimate writing, since the author, in addition to the first-person narrative from the title makes it clear that it is a vision particular about their country, attempting to resist the "male tyranny," breaking the silence for a long time the subject woman.